Teorema Titik Tetap Pada Ruang Quasi Metrik Terasing Tanpa Menggunakan Sifat Kekontinuan Fungsi - Malahayati, Mrs. (UIN Sunan Kalijaga Yogyakarta, 2014)
Dislocated quasi metric spaces is spaces with distance function that only satisfies two conditions from four conditions of distance function in metric spaces. Every metric spaces is dislocated quasi metric spaces, but the convers not satifies, so the characters that satisfies in metric spaces may not satisfies in dislocated quasi metric spaces.Â This paper is to recite fixed point theorems without continuity of any mapping in dislocated quasi metric spaces, also gives an example using the theorems that has recited